Jezikovni priročniki kot pomoč pri uspešni zeleni komunikaciji (ob primeru čebelarske terminologije) - Valh Lopert, Alenka; Zemljak Jontes, Melita (Komuniciranje okoljske krize, 2025)
This paper draws on the project ZELEN.KOM – Communicating the Climate Crisis for a Successful Transition to a Green Society. In the theoretical section, we highlight the importance of the Slovene language, with a special focus on professional usage, we examine the accessibility of general dictionaries that include terminological labels, the role of terminological dictionaries, and the use of language corpora, we introduce the Glossary of One Hundred Terms, developed as part of the project. The empirical section uses beekeeping terminology as a case study to illustrate how vocabulary can be introduced to preschool children, we analyze the use of the terminological qualifier beekeeping in key linguistic resources, including the Dictionary of the Slovenian Language2, Slovenian Orthography, the Beekeeping Terminological Dictionary, and address common orthographic issues. The paper thus intertwines the pedagogical aspect (i.e. the acquisition of professional terminology and early awareness of nature) and the linguistic aspect (i.e. the theoretical basis and orientation for the consistent, normative use of professional terminology) to critically reflect the linguistic norm and the vertical connection between theory and practice in building effective sustainable environmental communication and social responsibility.